Effect of Probiotics and Herbal Products on Intestinal Histomorphological and Immunological Development in Piglets - Daiga Gāliņa; Līga Ansonska; Anda Valdovska (Veterinary Medicine International)
The aim of the study was to evaluate the effect of probiotics and herbal products on the intestinal histomorphological and immunological development in piglets. Accordingly, 2-week-old piglets were allocated in 4 groups: C (basal diet), Pro (basal diet + probiotics), Pro+B (basal diet + probiotics + buckwheat bran), and H (powder of herbs). After 6 weeks of the experiment, 4 piglets from each experimental group were randomly selected and slaughtered at a slaughterhouse. Samples of tissue and digestive content from the jejunum and colon were collected for bacteriological, histological, and immunohistochemical examination. The results showed that probiotics increased the number of Lactobacillus spp. in the small p<0.05 and large intestines. The intestinal histomorphology was improved p<0.05 in all experimental groups by an increased villus height, VH : CD ration, colon crypt depth, and number of Ki-67+ epithelial cells. A higher number p<0.05 of goblet cells and their acidification were observed in group Pro, while the density of goblet cells was decreased by the herbs. Probiotics increased p<0.05 the number of intraepithelial lymphocytes (IELs), density of CD3+ cells in Peyer’s patches (PPs), and lamina propria (LP). In group H, a dual effect on the CD3+ cell distribution was observed. The herbs reduced p<0.05 the number of IELs and CD3+ in LP but increased the distribution of CD3+ cells in PPs. In the colon, herbs increased CD3+ cells in LP as well. It suggests that probiotics and herbs had influence on the intestinal histomorphology and the ability to modulate the mucosal immune system; however, the combination of probiotics and buckwheat bran was not so convincing, probably due to the inhibitory effect of the buckwheat bran on the probiotics used.